Trade Liberalization Impact on the Indonesian Palm Oil Industry - Ernawati, (2004)
The palm oil industry has been an important sector in the Indonesian economy for the past three decades. The important role of this industry to the Indonesian economy is not only due to the fact that Indonesia today depends substantially on oil palm for its foreign exchange earnings, but also because Indonesia is the largest consumer of palm oil among developing countries. This study was conducted to analyze the implications of various trade liberalization policies (reduction of export duty and import tariff) on the Indonesian palm oil industry. An econometric approach, mainly the error correction model on a simultaneous equation model, was employed. The model incorporated specific equations for acreage, harvested area, yield, domestic demand, rest of the world excess supply, Indonesian excess demand to India, China, Europe, and rest of the world, rest of the world excess demand and export price. The model was estimated using error correction and simultaneous model technique. Then the model was estimated by the two stage least squared (2SLS) method. The structural equations were assessed based on the economic and statistical criteria. The economic criteria were evaluated based on the signs and magnitude of the hypotheses, while the statistical criteria used the coefficient of multiple determination (R~)t,h e F statistic, auto correlation (h statistic), and t ratios to assess the model. Validation of the model was undertaken using Theil's inequality coefficient and root mean percentage square error. The results show that the net social welfare effects of export duty reduction at 10% showed a net gain for $ 857.56 thousand, which can be explained by gains in Indonesian producer surplus as a result of higher prices and by transfemng the production resources from palm oil production to more efficient sectors. Indonesian consumers' surplus decreased by $12.89 million, while Indonesian producers' surplus gained $17.38 million. On the other hand, when import tariff was reduced by lo%, the estimation yielded a gain in Indonesian producers7 surplus of $ 5.42 million, a gain of $ 1.38 million in efficiency attributable to the transfers of production resources to more efficient sectors and a loss in consumer surplus of $4.04 million due to increased production at higher prices. These numbers increased along with the increase in the percentage reduction of export duty. Reduction in both export duty and import tariff has the same implication as individually reducing export duty and import duty. Producer surplus increased by $ 22.83 million and efficiency gain rose by $ 1.51 million, meanwhile the loss in consumer surplus was $16.54 million. Then, the calculations of the welfare effects showed that the Indonesian palm oil industry will be better off without any intervention.